Effect of Isotopic Label on Buoyant Density Determinations of Viral DNA in the Preparative Ultracentrifuge - Cassai, Enzo (1973)
The buoyant density of herpes simplex virus DNA may be significantly increased by isotopic labeling, particularly with (14)C. The apparent increase in buoyant density may be readily calculated from the specific activity of the DNA and is easily demonstrated by isopycnic centrifugation in both the preparative and analytical centrifuge.